The level of antioxidant enzymes, plasma vitamins C and E in cement plant workers - Aydin, S; Aral, I; Kilic, N; Bakan, I; Aydin, S; Erman, F (Elsevier, 2004)
Background: Chronic exposure to cement dust has been reported to lead to several health problems. This study was designed to investigate the plasma oxidant and antioxidant status in cement plant workers and control subjects. Methods: Twenty-eight volunteer male cement plant workers and 30 volunteer office male workers (control) aged 29-54 years participated. The concentration of plasma vitamin C (P-VC), plasma vitamin E (P-VE), plasma malondialdehyde (P-MDA), and the activity of erythrocyte superoxide dismutase (E-SOD), plasma glutathione peroxidase (P-GSH-Px), and some serum biochemical parameters were measured in both groups. Results: The levels of MDA (175%), ALT (61%), and AST (39%) were significantly increased, while total RBC count (12%), Hb (11%) vitamin E (51%), C (35%), SOD (44%), and GSH-Px (51%) activities were markedly decreased, and the levels of urea, protein, and albumin triglyceride and cholesterol were almost the same in cement plant workers versus the control subjects. Conclusion: Cement workers are exposed to more oxidative stress compared to control subjects. To overcome these oxidative stresses, supplementation of antioxidant vitamins, such as alpha-tocopherol and ascorbic acid, may be beneficial. In addition, proper precaution to protect workers could prevent serious health problems. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: cement workers.; lipid peroxidation; antioxidant; free radical scavenging enzymes